A Love Triangle Between God, Sophia, and the Righteous Interwoven in the Retelling of the Pentateuchal Stories in Wisdom 10 - Geyser-Fouché, Ananda (2021)
In the Wisdom of Solomon, with special reference to chapters 6 to 10, wisdom is personified as a woman. This image is quite often found, especially in the wisdom literature. In the Wisdom of Solomon, Sophia is portrayed as a person who can speak, act, and feel, but most of all someone who can be loved and desired. She is portrayed as someone that is loved alternately by God and by the righteous. In Wisdom 10 Sophia is interwoven in the retelling of the Pentateuchal stories. She is the reason the righteous forefathers made the correct decisions, she protected and preserved them and gave them power, while the unrighteous are portrayed as leaving her and consequently making the wrong decisions. It is also interesting to notice the development in the concept of both wisdom and retribution from the traditional perspectives.
Keywords: Sophia; Wisdom; Wisdom of Solomon; Retribution